Limit analysis of geometrically hardening composite steel-concrete systems = Stany graniczne geometrycznie wzmacniających się konstrukcji zespolonych - Alawdin, Piotr; Urbańska, Krystyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper considers some results of creating load-carrying composite systems that have uprated strength, rigidity and safety, and therefore are called geometrically (self-) hardening systems. The optimization mathematic models of structures as discrete mechanical systems withstanding dead load, monotonic or low cyclic static and kinematic actions are proposed.
Keywords: obciążenia graniczne; konstrukcje zespolone; systemy samo-wzmacniające; optymalizacja; limit analysis; composite structures; geometrically hardening system; optimisation